2010
DOI: 10.1002/jmri.22065
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to high‐field MRI does not affect cognitive function

Abstract: Purpose: To assess potential cognitive deficits under the influence of static magnetic fields at various field strengths some studies already exist. These studies were not focused on attention as the most vulnerable cognitive function. Additionally, mostly no magnetic resonance imaging (MRI) sequences were performed. Materials and Methods:In all, 25 right-handed men were enrolled in this study. All subjects underwent one MRI examination of 63 minutes at 1.5 T and one at 7 T within an interval of 10 to 30 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…To date, after more than 500 million MRI examinations worldwide, of which more than one thousand examinations were conducted at 4, 7 or 8 T, no indications of any long term health effects on humans have been observed. New studies show that the static magnetic field affects neither vital signs nor neurocognitition [20][21][22][23][24]. The findings in this work support the efforts which are currently being taken to amend the exposure limits for high fields and ultra high fields at MRI.…”
Section: Resultssupporting
confidence: 87%
“…To date, after more than 500 million MRI examinations worldwide, of which more than one thousand examinations were conducted at 4, 7 or 8 T, no indications of any long term health effects on humans have been observed. New studies show that the static magnetic field affects neither vital signs nor neurocognitition [20][21][22][23][24]. The findings in this work support the efforts which are currently being taken to amend the exposure limits for high fields and ultra high fields at MRI.…”
Section: Resultssupporting
confidence: 87%
“…A more recent study has also shown that different cognitive domains can also be affected by time-varying magnetic fields [7]. In line with proposed biological mechanisms for these effects [8,9] no effects were observed within the homogeneous magnet bore, where patients are located during scanning [10] nor were effects on cognition measurable immediately after exposure had ended [11]. However, recent data from a controlled trial using transcranial magnetic stimulation (TMS) does suggest a transient alteration in cortical excitability after undergoing an MRI scan and exposure has ended [12].…”
mentioning
confidence: 73%
“…Previous studies revealed no significant biological effects on humans in terms of vital signs or cognitive functions; [2][3][4][5][6][7][8][9] however, some transient sensations, such as vertigo and a metallic taste, are said to be more frequently experienced at 7T than at lower static magnetic fields. 8,10 -12 Three studies performed with large European cohorts and 7T scanners from 2 vendors demonstrated that approximately one-fourth of subjects experienced unpleasant sensations, most of whom found the sensations tolerable.…”
Section: Introductionmentioning
confidence: 99%